Cross-cultural questionnaires and the necessity of using native translators : a Croatian-Swedish case - Molander, Bo (Array, 2020)
In this paper, we discuss problems of comparing two European cultures in a study of emotional intelligence by relying on traditional back translation of the questionnaire and the scales used in the study (Holmström, Molander, & Takšić, 2008; Molander, Holmström, & Takšić, 2009, 2011). We compared Croatian and Swedish university students in using The Emotional Skills and Competence Questionnaire, which is an original Croatian questionnaire (Takšić, 1998; Takšić, Mohorić, & Duran, 2009) based on the emotional intelligence theory of Mayer and Salovey (1997). Initially, we found small differences in responding to emotional items between the two countries as revealed by traditional statistical methods. Here we illustrate a large increase of the initial differences by applying differential item functioning (DIF) procedures (Zumbo, 1999), and then reducing again differences by taken several important steps in analyzing the translated items. Most important in these latter procedures was a new translation to Swedish by a native Croatian-speaking translator.